Facilitatory and inhibitory effects of Kinesio tape: Fact or fad?. Issue 2 (February 2016) - Cai, C.; Au, I.P.H.; An, W.; Cheung, R.T.H.
Abstract: Objectives: Kinesio tape (KT) is a commonly used intervention in sports. It claims to be able to alter the muscle activity, in terms of both facilitation and inhibition, by certain application methods. This study compared the neuromuscular activity of the wrist extensor muscles and maximal grip strength with facilitatory, inhibitory KT, and tapeless condition in healthy adults who were ignorant about KT. Potential placebo effects were eliminated by deception. Design: Randomized deceptive trial. Methods: 33 participants performed maximal grip assessment in a randomly assigned order of three taping conditions: true facilitatory KT, inhibitory KT, and no tape. The participants were blindfolded during the evaluation. Under the pretense of applying a series of adhesive muscle sensors, KT was applied to their wrist extensor muscles of the dominant forearm in the first two conditions. Within-subject comparisons of normalized root mean square of the wrist extensors electromyographic activity and maximal grip strength were conducted across three taping conditions. Results: 31 out of 33 enlisted participants were confirmed to be ignorant about KT. No significant differences were found in the maximum grip strength ( p = 0.394), electromyographic activity ( p = 0.276), and self-perceived performance ( p = 0.825) between facilitatory KT, inhibitory KT, and tapeless conditions. Conclusions: Neither facilitatory nor inhibitory effects were observed between different application techniques of KT in healthy participants. Clinically, alternative method should be used for muscle activity modulation.